(untitled) (Revista de Ciências Agroveterinárias, 2025)
Cassava (Manihot esculenta Crantz) plays a key role in Brazilian agriculture, but its genetic variability is under threat, requiring effective conservation strategies. This study aimed to evaluate the impact of polyethylene glycol (PEG) and silver nitrate (AgNO₃) on the in vitro conservation of the regional variety ‘Amarelona’, with a view to identifying concentrations that favor the maintenance of plant viability and controlled growth. Four concentrations of PEG (5, 10, 20, and 40 g/L) and two concentrations of AgNO₃ (5 and 10 mg/L) were applied, in addition to a control, in an experiment with seven treatments and 24 replicates, conducted for up to 180 days. The analyses included shoot height, number of leaves and shoots, root length, and fresh and dry mass of the shoot and root parts. The results showed that a concentration of 10 g/L PEG was the most effective for maintaining vegetative growth with long-term viability, while higher doses led to inhibition and senescence. AgNO₃, on the other hand, had negative effects in both concentrations, resulting in the death of plants throughout the experiment. It is concluded that PEG at 10 g/L is a promising solution for the in vitro conservation of cassava, ensuring the maintenance of viability, while the use of AgNO₃ at the concentrations tested severely compromised plant vitality.